APLIKASI HUKUM PIDANA ISLAM DALAM PENANGGULANGAN PENYALAHGUNAAN NARKOTIKA YANG DILAKUKAN OLEH ANAK DI DESA MENANGA TENGAH KEC. SEMENDAWAI BARAT KAB. OKU TIMUR - Munawaroh Munawaroh; Muhammad Rizal; Zuraidah Zuraidah (Tazir, 2024)
Children are an inseparable part of the survival of humans, nations and countries. Children are a trust of Allah SWT who must always be looked after and protected because in children there is inherent honor, dignity and rights as human beings which must be upheld. Recently, 10% of the 835 children in Central Menanga Village have consumed narcotics. Therefore, this research aims to find out two things: First, how to prevent narcotics abuse by children in Central Menanga Village? and Second, How is Islamic Criminal Law Applied in Combating Narcotics Abuse by Children? This research is field research and the type of data used is qualitative data. The data collection technique uses direct interview techniques with informants who are deemed necessary and related to the problem being studied by means of question and answer. The results of the research concluded that overcoming narcotics abuse by children is to provide sanctions against child perpetrators through juvenile justice/diversion, then the community, parents and religious leaders together to provide understanding to children about the dangers of narcotics and eradicate those who use/distribution narcotics. In Islamic criminal law, narcotics abuse by children is included in the category of judimah, therefore the perpetrator can be punished, as an effort to prevent other children from participating and provide education to children who have committed narcotics abuse. The age limit for children aged 7-14 years can be subject to educational punishment (ta'dib), children aged 15 years and over can be subject to qisas, hudud and ta'zir punishments. Keywords: Children, Narcotics Control, Narcotics, Islamic Criminal Law